Autoimmune neonatal thrombocytopenia secondary to maternal idiopathic thrombocytopenic purpura: A case report (Research, Society and Development, 2024)
Thrombocytopenia is defined as a platelet count of less than 150,000/mm3, through blood collected with EDTA, and its occurrence is around 18% to 35% of newborns in the Neonatal ICU, with 80% occurring in the first week of life, commonly in extremely premature newborns, weighing